Knowledge Technology - Gierl, Martin (Historical Studies on Central Europe, 2025)
Language – writing – printing – media communication—regulated flow of information: Academic knowledge is about technology. Knowledge is shaped by the regulation of information flows. The discourse of authors is a fundamental part of these regulations, but only a part. Knowledge is not the result of discourse but of organisation. The essay uses the university system, the journal system, the Turing-machine and Lichtenberg’s physics to prove this. It shows how quality, coherence, progressive diversity, sustainable permanence, and mechanisms for testing, reproducing, transmitting, and supplementing what has been achieved emerge from organised quantity. The thesis of the essay is that academic knowledge is a technology that continues to produce technology.